Development of soft magnetic composites cast from ferrites and construction binders with lowest core loss - Ibrahim Ellithy; Mauricio Esguerra; Rewanth Radhakrishnan (AIP Advances)
Soft magnetic composites cast with recycled ferrites and construction binders like cement, epoxy, or asphalt are highly robust and possess the lowest core up to 100 kHz in a wide temperature range. This paper shows how by using precision-enhanced magnetic testing and sophisticated hysteresis modeling, the performance of these materials could be significantly improved with respect to the stress effect on losses. A composite material grade with minimal losses was developed by benefiting from the behavior of ferrite compositions yielding zero crystalline anisotropy at temperatures below 0 °C under compressive stress.